Demystifying jadeite: an underwater Maya discovery at Ek Way Nal, Belize. (10th April 2019) - McKillop, Heather; Harlow, George; Sievert, April; Smith, C. Wayne; Wiemann, Michael C.
Abstract: Abstract : Jadeite artefacts at Maya sites are normally associated with ritual and ceremonial locations, with high-quality jadeite reserved for elite objects. The discovery of a jadeite gouge with a wooden handle at a Classic Maya salt-working site submerged by sea-level rise—Ek Way Nal, Belize—is therefore unexpected and provides new information about the utilitarian use of this stone. The extremely high quality of this jadeite tool is particularly surprising, offering new insight into the Classic Maya exchange systems and the role of salt makers such as those based at Ek Way Nal.